Zero valent iron mediated degradation of the pharmaceutical diazepam - Bautitz, Ivonete Rossi [UNESP]; Velosa, Adriana C. [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Parameters that influence the zero valent iron mediated degradation of the pharmaceutical diazepam (DZP) were evaluated including the iron concentration and its pre-treatment, the effect of complexation with EDTA and oxic versus anoxic condition. It was observed that acid pre-treatment of iron particles is important for degradation efficiency and that H2SO4 is a better choice than HCl, resulting in higher degradation of DZP. Under oxic conditions, the degradation of DZP achieved 96% after 60 min using Fe-o (25 g L-1) pre-treated with H2SO4 in the presence of EDTA (119 mg L-1), while mineralization achieved around 60% after the same time. Under anoxic conditions, degradation occurred, however at lower extent, achieving 67% after 120 min. The addition of EDTA improved the treatment efficiency in 20% leading to 99% DZP degradation after 120 min. The first intermediates formed during DZP degradation were identified using LC/MS analysis and revealed the formation of mono- and di-hydroxylated products from DZP during Fe-o/EDTA/O-2 degradation, which evidences that OH was the main oxidizing species formed in this process. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Emerging contaminants; Degradation; Zero valent iron; Fenton